Assessment of Spleen Stiffness Using Acoustic Radiation Force Impulse Imaging (ARFI): Definition of Examination Standards and Impact of Breathing Maneuvers - Karlas, T.; Lindner, F.; Tröltzsch, M.; Keim, V. (Ultraschall in der Medizin - European Journal of Ultrasound, 2014)
Purpose: Spleen elastography is a promising method for the characterization of portal hypertension in cirrhotic individuals. However, standardized examination procedures for spleen stiffness measurement have not been defined yet. We analyzed the distribution characteristics of spleen shear-wave velocity (ARFI) and assessed the influence of the respiratory position on spleen stiffness measured by ARFI.Materials and Methods: 25 healthy probands and 25 patients with Child A liver cirrhosis were prospectively characterized with conventional ultrasound, transient elastography, liver ARFI, and underwent spleen ARFI in two respiratory positions: breath hold after expiration (exp) and deep inspiration (insp). For each position 20 single measurements were performed. The distribution of spleen ARFI values was analyzed for normality and the appropriate number of measurements for spleen stiffness estimation was investigated.Results: Spleen ARFI results were normally distributed in > 95 % of cases. Performing 20 instead of 10 single measurements resulted in < 5 % deviation from the mean value after 20 measurements in the majority of cases. Cirrhotic patients had a higher spleen stiffness compared to healthy probands (exp: 3.25 ± 0.58 vs. 2.46 ± 0.35 m/s; p < 0.001). Deep inspiration caused an overall increase in spleen stiffness in both groups: probands 2.46 ± 0.35 m/s (exp) vs. 2.66 ± 0.36 m/s (insp), p = 0.01; cirrhotics 3.25 ± 0.58 m/s (exp) vs. 3.46 ± 0.38 m/s (insp), p = 0.03. However, cases with high spleen stiffness values (exp) show decreasing ARFI values in deep inspiration.Conclusion: ARFI values of the spleen are normally distributed and the mean of 10 valid measurements can be used as a representative value. Deep inspiration significantly modulates spleen stiffness. Therefore, the respiratory position needs careful standardization.
Keywords: ARFI; liver cirrhosis; portal hypertension; spleen stiffness; ultrasound